IMPLEMENTASI PEMBELAJARAN BERBASIS AKTIVITAS MOTORIK UNTUK ANAK USIA DINI DENGAN GANGGUAN ADHD DI PAUD KB AR RAUDHAH DESA BANTARSARI KECAMATAN BUNGURSARI KOTA TASIKMALAYA - Irma Latipatul Mar'ah; Sofia Ratna Awaliah Fitri; Saeful Milah (CV. Kalimasada Group, 2025)
Early childhood students with ADHD require creative learning approaches that match their developmental characteristics. This disorder causes difficulties in focusing, controlling impulses, and following rules; therefore, a strategy that channels excess energy and enhances attention is essential. Motor activity-based learning is an effective alternative because it integrates physical movement with children’s cognitive, social, and emotional processes. This study aims to describe the planning, implementation, outcomes, and inhibiting factors of motor activity-based learning for children with ADHD at PAUD KB Ar Raudhah, Bantarsari Village, Bungursari District, Tasikmalaya City. The research used a qualitative descriptive method involving three children with ADHD, teachers, and parents. Data were collected through observation, interviews, and documentation. The findings show improvements in children’s focus, self-control, and social interaction after engaging in simple motor activities such as running and ball games. Supporting factors include teacher competence and parental involvement, while inhibiting factors consist of limited facilities, time, and teacher training. Motor activity-based learning effectively helps children with ADHD adapt better in the learning environment.